A note on the hypercomplex riemann-cauchy like relations for quaternions and laplace equations - Marão, José Antonio Pires; Borges Neto, Manoel Ferreira [UNESP] (Academic Publications, 2014)
In this Note it is worked out a new set of Laplace-Like equations for quaternions through Riemann-Cauchy hypercomplex relations otained earlier [1]. As in the theory of functions of a complex variable, it is expected that this new set of Laplace-Like equations might be applied to a large number of Physical problems, providing new insights in the Classical Fields Theory.
Keywords: quaternions, Laplace's equations, Riemann-Cauchy relations